Alternative Retirement Paths and Cognitive Performance: Exploring the Role of Preretirement Job Complexity. (9th July 2019) - Carr, Dawn C; Willis, Robert; Kail, Ben Lennox; Carstensen, Laura L
Abstract: Background and Objectives: Recent research suggests that working longer may be protective of cognitive functioning in later life, especially for workers in low complexity jobs. As postretirement work becomes increasingly popular, it is important to understand how various retirement pathways influence cognitive function. The present study examines cognitive changes as a function of job complexity in the context of different types of retirement transitions. Research Design and Methods: We use data from the Health and Retirement Study (HRS) to examine change in cognitive function for workers who have held low, moderate, and high complexity jobs and move through distinct retirement pathways—retiring and returning to work, partial retirement—compared with those who fully retire or remain full-time workers. Inverse probability weighted regression adjustment (a propensity score method) is used to adjust for selection effects. Results: There are systematic variations in the relationships between work and cognitive performance as a function of job complexity and retirement pathways. All retirement pathways were associated with accelerated cognitive decline for workers in low complexity jobs. In contrast, for high complexity workers retirement was not associated with accelerated cognitive decline and retiring and returning to work was associated with modest improvement in cognitive functioning. Discussion and Implications: Both policy makers and individuals are beginning to embrace longer working lives which offer variety of potential benefits. Our findings suggest that continued full-time work also may be protective for cognitive health in workers who hold low complexity jobs.